Alignment of Common Wheat and Other Grass Genomes Establishes a Comparative Genomics Research Platform - Sun, Sangrong; Wang, Jinpeng; Yu, Jigao; Meng, Fanbo; Xia, Ruiyan; Wang, Li; Wang, Zhenyi; Ge, Weina; Liu, Xiaojian; Li, Yuxian; Liu, Yinzhe; Yang, Nanshan; et al. (Frontiers in Plant Science, 2017)
Grass genomes are complicated structures as they share a common tetraploidization, and particular genomes have been further affected by extra polyploidizations. These events and the following genomic re-patternings have resulted in a complex, interweaving gene homology both within a genome and between genomes. Accurately deciphering the structure of these complicated plant genomes would help us better understand their compositional and functional evolution at multiple scales. Here, we build on our previous research by performing a hierarchical alignment of the common wheat genome vis-à-vis eight other sequenced grass genomes with most up-to-date assemblies and annotations. With this data, we constructed a list of the homologous genes and then, in a layer-by-layer process, separated their orthology and paralogy that were established by speciations and recursive polyploidizations, respectively. Compared with the other grasses, the far fewer colinear outparalogous genes within each of three subgenomes of common wheat suggest that homoeologous recombination and genomic fractionation should have occurred after its formation. In sum, this work contributes to the establishment of an important and timely comparative genomics platform for researchers in the grass community and possibly beyond. Homologous gene list can be found in Supplemental material.